OPTIMIZED PRODUCTION OF L-ARGINASE: A TUMOUR INHIBITOR ISOLATED FROM MARINE BACTERIA - RAHAMAT UNISSA; M. SUDHAKAR; A. SUNIL KUMAR REDDY (International Journal of Pharma and Bio Sciences, 2015)
Our objective is to study l-arginase production pattern under submerged fermentation using novel marine isolate Idiomarina sediminum; H1695 (Gene Bank Accession Number JF346667) . Idiomarina sediminum; H1695 is a gram negative rod shaped marine bacteria isolated from chirala beach of Andhra Pradesh . It was screened for the enzyme production in mineral arginine medium. Further the activity was confirmed calorimetrically by estimating the levels of urea . The potential of an isolated novel strain for L-arginase production was analyzed under submerged fermentation with different process parameters and medium constituents. The maximum yield of enzyme production (215.36U/ml) was achieved in a seawater based medium at pH 9, 37°C, 10% inoculum concentration and 2% l-arginine concentration for 120 h. The medium when supplemented with carbon source, it improved the enzyme production from 121.49 to 158.37 U/ml with 1.5% maltose. Addition of 2% casein also improved the L-arginase production (168.23) .The overall production of the enzyme after optimization was increased to 215.36U/ml which is twice the original. This novel strain has immense potential as an industrial organism for the production of L-arginase as extracellular enzyme employing submerged fermentation. Further, it was observed that from the course of the present study, sea water could be used as an ideal fermentation medium for L-arginase production